A Breakthrough in Hemostatic Agents For Dentistry: Will They Be a Game Changer? - Ghoshal , Dr. Nanda kishore (Medical Science Journal for Advance Research, 2025)
Background: Bleeding can occur during or after surgery which can be troublesome for both patient and the surgeon and if uncontrolled can lead to serious life threatening consequences. Bleeding may also compromise visibility Hemostatic agents provide control of external bleeding by enhancing the natural clotting process via various physical reactions between the agent and blood factors. Various hemostatic agents like Hemcon® (chitosan-based), TraumaDEX® (Potato starch based microparticles), QuickClot® (zeolite-based), STARSIL Hemostat, SURGISPON, CELOX BioHemostat etc, are available which have proved their effectiveness in major surgeries (Cardiothorasic, Urological, Abdominal, etc). They have been successfully introduced in the field of dental surgery recently, which is a boon in major and minor maxillofacial surgical procedures. Conclusion: The local hemostatic agents may be a great help in providing clear and bloodless field, alleviating patient anxiety, and improving patient-surgeon compliance. Newer agents are really a breakthrough in the surgical procedures, and further research is still going on for future betterment. This will be a great news for dental surgeons as bleeding is always one of the major complications in dentistry, and dentists face the problem routinely.